Pendampingan Tahfidz Al-Qur’an Putra di Desa Dabung Geger Bangkalan - Shonhaji Shonhaji; Umar Zakka; Ahmad Bahrudin (Pusat Riset dan Inovasi Nasional, 2022)
Assistance for tahfidz al-Qur'an in Dabung village, the formulation of the problem raised from this research is the effectiveness and maximization of tahfiẓ Al-Qur'an assistance in Dabung Geger Bangkalan village. The purpose of holding this Tahfiẓ al-Qur'an program mentoring activity is to increase the effectiveness and maximize the tahfiẓ al-Qur'an program in Dabung village. Because the program is filled with conveying methods for memorizing the Qur'an properly and correctly. The benefits expected in this service program are: Can be a motivation and additional knowledge for academics to be more active in developing education, Adding patterns of application methods in memorizing the Qur'an in Dabung Geger village. Encouraging the community to be more happy with al-Qur'an Koran. Alternative problem solving is done by establishing a new method in carrying out Tafiẓ al-Qur'an activities in the village of Dabung. The new method used is to divide the implementation time into two parts, as follows: The first is the rote deposit activity (04:30-06:00) and the joint murajaah activity (18:15-19:30).